2007
DOI: 10.1111/j.1443-9573.2007.00278.x
|View full text |Cite
|
Sign up to set email alerts
|

Using serum pepsinogens wisely in a clinical practice

Abstract: Serum pepsinogen (PG) has been used as biomarkers of gastric inflammation and mucosal status, including atrophic change, before the discovery of Helicobacter pylori (H. pylori). Serum pepsinogen I (PG I) and pepsinogen II (PG II) levels are known to increase in the presence of H. pylori-related nonatrophic chronic gastritis. The measurement of serum PG provides much information on the presence of intestinal metaplasia as well as atrophic gastritis. The eradication of H. pylori provokes a significant change in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
78
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(84 citation statements)
references
References 56 publications
5
78
1
Order By: Relevance
“…When it came to the atrophic lesion from the non-atrophic lesion, both PGⅠand PG Ⅱ levels had a trend to go down, suggesting that the PG Ⅰ/Ⅱ ratio reflects the development of atrophic lesion on gastric membranes better than either PGⅠor PGⅡ alone. The PGⅠ/Ⅱ values for atrophic gastritis were significantly lower than those for NOR and non-atrophic lesions, while there was no difference among these atrophic lesions, suggesting that the PGⅠ/Ⅱ ratio is an effective parameter for screening individuals at high risk of GC [9,[24][25][26][27] . We obtained the best cut-off points of the PG Ⅰ/Ⅱ ratio for detecting GC and its precursors by ROC curve with a sensitivity of 53.2% and a specialty of 67.5%, which can be used for further investigation as a screening tool in the first period.…”
Section: Discussionmentioning
confidence: 99%
“…When it came to the atrophic lesion from the non-atrophic lesion, both PGⅠand PG Ⅱ levels had a trend to go down, suggesting that the PG Ⅰ/Ⅱ ratio reflects the development of atrophic lesion on gastric membranes better than either PGⅠor PGⅡ alone. The PGⅠ/Ⅱ values for atrophic gastritis were significantly lower than those for NOR and non-atrophic lesions, while there was no difference among these atrophic lesions, suggesting that the PGⅠ/Ⅱ ratio is an effective parameter for screening individuals at high risk of GC [9,[24][25][26][27] . We obtained the best cut-off points of the PG Ⅰ/Ⅱ ratio for detecting GC and its precursors by ROC curve with a sensitivity of 53.2% and a specialty of 67.5%, which can be used for further investigation as a screening tool in the first period.…”
Section: Discussionmentioning
confidence: 99%
“…In cases of gastroduodenal diseases, especially gastric cancer, the pathogenesis involves three major factors: H. pylori virulence factors, host factors, and environmental factors (1,10,14,16,21,34,57). Two H. pylori virulence factors that have been focused on in many studies all around the world are VacA and CagA.…”
mentioning
confidence: 99%
“…These mechanisms were investigated by measuring the levels of PGI, a practical biomarker in the determination of the status of the gastric mucosa. 19 An earlier report showed that low PGI values indicate progression of mucosal atrophy. 20 In this study, the level of PGI was significantly higher in the AA genotype than in the AG+GG genotype, suggesting that genotypes causing higher GST-M3 activity are involved in protection from mucosal atrophy progression.…”
Section: Discussionmentioning
confidence: 99%